Effects of administering berberine alone or in combination on type 2 diabetes mellitus: a systematic review and meta-analysis - Wang, Jiacheng; Bi, Chenhao; Xi, Hongbin; Wei, Fengqin (Frontiers in Pharmacology, 2024)
Background Despite the availability of multiple therapies for Type 2 diabetes mellitus (T2DM), challenges remain due to side effects and efficacy limitations. Berberine (BBR) has shown broad anti-diabetic effects, prompting a systematic assessment of its efficacy and safety through a meta-analysis. Methods A comprehensive search was conducted across eight database and search engines from inception until 06/09/2024. Only randomized controlled trials (RCTs) meeting inclusion criteria were analyzed. The Cochrane risk of bias assessment tool and Jadad scale were used to evaluate study quality. Meta-analysis was performed using RevMan v5.3 and Stata/SE v15.1. Results Fifty studies involving 4,150 participants were included. BBR alone significantly reduced fasting plasma glucose (FPG) (MD = −0.59 mmol/L, p = 0.048), 2-h postprandial blood glucose (2hPBG) (MD = −1.57 mmol/L, p < 0.01), low-density lipoprotein cholesterol (LDL-C) (MD = −0.30 mmol/L, p < 0.01), total cholesterol (TC) (MD = −0.30 mmol/L, p = 0.034), and triglycerides (TG) (MD = −0.35 mmol/L, p < 0.01). When combined with hypoglycemic drugs, BBR significantly improved FPG (MD = −0.99 mmol/L, p < 0.01), 2hPBG (MD = −1.07 mmol/L, p < 0.01), glycated hemoglobin (HbA1c) (MD = −0.69%, p < 0.01), and other metabolic markers, including fasting insulin (Fins), homeostasis model assessment index for assessing insulin resistance (HOMA-IR), lipid profiles and inflammatory markers. The most common BBR dosage was 0.9–1.5 g/d, with treatment cycles typically lasting 1–3 months. Conclusion Current evidence suggests that BBR alone or in combination has significant potential for treating type 2 diabetes mellitus (T2DM). Future research should encompass a broader scope, including not just the beneficial effects of BBR in head-to-head studies, but more crucially, delving into its mechanisms of action with hypoglycemic drugs to optimize T2DM treatment strategies.